Keberagaman kebudayaan dan tantangannya di Indonesia: Diversity, culture, Multiculturalisme, social - laras, flower kharisma (Maliki Interdisciplinary Journal, 2026)
Indonesia is the largest archipelagic country in the world and possesses extensive cultural diversity, including more than 600 ethnic groups, over 700 local languages, and various religions and traditions. This diversity forms a core element of national identity, as reflected in the principle of Bhinneka Tunggal Ika (Unity in Diversity). However, cultural diversity also presents challenges, such as potential social conflict arising from ethnic and religious differences, the growth of intolerance and radicalism, and cultural homogenization driven by globalization and urbanization. Regional development disparities further contribute to socio-economic inequality, which may weaken national cohesion, while cultural heritage preservation faces threats including site degradation and limited conservation efforts. This study emphasizes the importance of inclusive and collaborative strategies to address these challenges. Multicultural education is essential in promoting tolerance and respect for diversity, while digital technology can support the documentation and promotion of local cultures. In addition, public policies that encourage economic equity and intergroup dialogue play a vital role in strengthening social integration. Through sustainable and inclusive approaches, Indonesia’s cultural diversity can become a strategic asset for national development.